[PP.10.16] RHEUMATOID ARTHRITIS PATIENTS WITH ARTERIAL HYPERTENSION HAVE HIGH PREVALENCE OF CARDIOVASCULAR RISK FACTORS. (September 2017) - Krougly, L.; Fomicheva, O.; Karpov, Yu; Popkova, T.; Nasonov, E.
Abstract : Objective: Tight control of disease activity, management of traditional CV risk factors such as arterial hypertension (AH), smoking, obesity, blood lipids level, diabetes mellitus (DM) are the most important steps in improving CV disease outcomes in Rheumatoid arthritis (RA) pts. We have studied prevalence of CV risk factors in RA pts with AH and management of risk factors. Figure. No caption available. Design and method: A total of 124 pts with RA on the ACR/EULAR criteria 2010 and suspected coronary artery disease (CAD) underwent clinical, laboratory and instrumental evaluation and treatment assignment. Pts were included in the study based on the clinical signs of CAD (chest pain) and CV risk factors evaluation. All pts underwent laboratory tests included blood total cholesterol (TC), LDL, HDL, TG, erythrocyte sedimentation rates (ESR), C-reactive protein (CRP), rheumatoid factor (RF), antibodies against citrullinated circular peptides (anti-CCP). We evaluated CV risk factors (AH, dyslipidemia, smoking, obesity), inflammation markers, anti-rheumatic treatment and treatment reduces CV risk. Results: Mean age was 59.0 years, men 29%, 25% smokers. AH had 98 pts (77%). Mean ESR was 24.9 mm/h, CRP 2.5 mg/dl, RF+ in 74%, anti-CCP+ in 66%. 83% had the very high CV risk according to the SCORE stratification or cardiovascular diseases. Methotrexate was prescribed in 52%, leflunomide 13%, hydroxychloroquine 5%, sulfasalazine 7%, biological anti-rheumatic drugs 26%, methylprednisolone in 51% (n = 63). RA remission (DAS28<3, 2 in 17%, 3, 2–5, 1 in 50%, >5, 1 in 33%). Pts with AH had mean blood pressure 127/69 mm Hg, pts without AH 123/72 mm Hg. 64% had treated by the combination of 3 antihypertensive drugs. Target level of blood pressure (<140/90 mm Hg) was achieved in 82%. Target level of LDL (<1.8 mmol/l) was achieved only in 18% of high CV risk pts). Statin (Atorvastatin, mean dose 13.7 mg/d) treatment was administrated in 73%. Age, sex, smoking status, inflammation markers didn't show any significantly differences. Conclusions: We found high prevalence of AH (77%) in RA which correlates with CV risk factors prevalence (obesity, DM, higher LDL). Pts achieved the target level of blood pressure more often than the target level of lipids.